The effect of large investors on asset quality: Evidence from subprime mortgage securities - Manuel Adelino; W. Scott Frame; Kristopher S. Gerardi (Federal Reserve Bank of Atlanta, 2014)
This paper examines how the government-sponsored enterprises (GSEs) Fannie Mae and Freddie Mac, the largest investors in subprime private-label mortgage-backed securities (PLS), influenced the risk characteristics and prices of the deals in which they participated. To identify the causal effect of the GSEs, we use the fact that PLS deals in which Fannie Mae and Freddie Mac purchased securities included separate mortgage pools: one specifically created for the GSEs and one or more others directed at other triple-A investors. Using within-deal variation, we find that the pools bought by Fannie Mae and Freddie Mac had similar ex-ante risk characteristics but performed much better ex-post relative to other mortgage pools in the same deals. These effects were concentrated in low-documentation loans and in issuers that were highly dependent on Fannie Mae and Freddie Mac. Our results extend the importance of disciplining effects of large claimholders beyond informationsensitive securities, such as equities and bank debt, to information-insensitive arm's-length debt.
Keywords: G17; G21; G23; 330; mortgage default; GSEs; securitization; private information